How to love brutalism - Grindrod, John (Batsford, 2018)
Whether you love or hate brutalist buildings, this book will explain what it is about them that elicits such strong feeling. You will understand the true power of concrete and of mammoth-sized buildings, but also some of the more subtle aspects of brutalist buildings that you may not have known or considered. The book journeys from the UK to discover brutalism and its influence around the world - from Le Corbusier's designs in Chandigarh, India, to Lina Bo Bardi's buildings in Brazil